Fabrication of bulk alumina structures with humidity sensing capabilities using direct ink write technique. Issue 4 (18th May 2021) - Renteria, Anabel; Garcia, Luisa F.; Diaz, Jorge A.; Delfin, Luis C.; Regis, Jaime E.; Reza, Elizabeth I.; Espalin, David; Tseng, Tzu-Liang Bill; Lin, Yirong
Abstract : Purpose: The purpose of this study is to evaluate different 3D structures for humidity sensing that will enable the fabrication of complex geometries with high moisture sensitivity. Design/methodology/approach: Humidity sensors based on alumina ceramics were fabricated using direct ink write (DIW) technique. Different engineered surface area, polymer binder ratio and post-processing treatment were considered to increase moisture sensitivity. Findings: It was found that the binder ratio plays an important role in controlling the rheology of the paste during printing and determining the pore size after post-processing treatment. The sensibility of the fabricated humidity sensor was investigated by measuring its capacitance response toward relative humidity (RH) varying from 40% to 90% RH at 25°C. It is shown that using 3D lattice design, printed alumina humidity sensor could improve sensitivity up to 31.6 pF/RH%, over an order of magnitude higher than solid alumina. Originality/value: Most of the alumina humidity sensors available are films in nature because of manufacturing difficulties, which limited its potential of higher sensitivity, and thus broader applications. In this paper, a novel 3D alumina humidity sensor was fabricated using DIW 3D printing technology.